Tunnel driving occupational environment and hearing loss in train drivers in China. Issue 2 (11th December 2018) - Peng, Yong; Fan, Chaojie; Hu, Lin; Peng, Shuangling; Xie, Pengpeng; Wu, Fugui; Yi, Shengen
Abstract : Objective: Hearing loss caused by high levels of noise is a potential occupational health disorder among train drivers around the world. This study aims to investigate the relationship between tunnel driving occupational environment and hearing loss in train drivers, to provide some insights into helping reduce hearing loss among train drivers. Methods: This study analysed cross-sectional data for 1214 train drivers who work at China Railway Guangzhou Group. Health examination was taken by physicians with professional licences, and audiometric testing was performed by health technicians in a sound-isolated room. T/R is defined as the ratio of the length of the tunnels to the length of the railway along drivers' work routes. Different multivariate models and stratified models were established for sensitivity analysis. A multivariable logistic regression model was used to estimate the ORs of hearing loss associated with tunnel driving occupational environment. Results: The adjusted OR for high-frequency hearing loss in association with the highest T/R levels (30%–45%) versus the lowest T/R levels (<15%) was 3.72 (95% CI 1.43 to 9.69). The corresponding OR for speech-hearing loss was 1.75 (95% CI 0.38 to 8.06). The sensitivity analysis shows our results are suitable for various alternative models. Conclusions: This study found that there was a significant association between tunnel driving occupational environment and hearing loss. Train drivers who work in a higher T/R environment have worse hearing loss.